Analysis of Red Brick Product Quality Improvement at UD. Batu Bata Bulan Using CRISP-DM and C4.5 Algorithm - Septiana, Widya; Tsani, Farhan; Utami, Silvia Firda; Andani, Rina Meri (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
UD Batu Bata Bulan is a home industry in Batu Bulan Village that produces red bricks. The industry has been operating for 20 years and has been producing bricks every day. The home industry is facing problems related to the quality of red bricks that require appropriate action to improve to meet the desired quality. In addition, the home industry is still experiencing difficulties in conducting product quality inspections due to the lack of inspection technology to help the process. The problems faced can be detrimental to UD. Batu Bata Bulan. Therefore, it is necessary to analyze the causes of defective products in the process of producing red bricks and improve the quality of red brick products. Therefore, the researcher conducted an analysis to address the problems that occurred in the company related to product quality. The solution that can be given is to classify the type of defective product using the role of data mining. In this study, the standard Cross Industry Standard Process For Data Mining (CRISP-DM) procedure and C.45 Algorithm were used in data processing.The result of this research indicate significant knowledge in classifying black color defect in data this could facilitate the quality inspection department in making accurate decisions.